Fitness-Dependent Effect of Acute Aerobic Exercise on Executive Function - Li, Lin; Zhang, Shu; Cui, Jie; Chen, Li-Zhen; Wang, Xiaoyan; Fan, Mingxia; Wei, Gao-Xia (Frontiers in Physiology, 2019)
Cognitive gains are reported to be induced by acute aerobic exercise, but the role of fitness in the effect of acute aerobic exercise on executive function remains unknown. Therefore, we aimed to examine the effect of fitness on acute exercise-induced changes in executive function from neural mechanism approach. Twenty-four female college students were assigned to high-fitness or low-fitness groups based on their cardiovascular fitness level, and then underwent functional magnetic resonance imaging while performing N-back tasks before and after 30 min of acute exercise. The behavioral results revealed significant interaction effects of group by time in the 0-back and 1-back tasks, but not in the 2-back task. The accuracy was significantly higher in the high-fitness group than in the low-fitness group before exercise in the 1-back and 2-back tasks. At the neural level, significant interaction effects of group by time were observed in all tasks. The 0-back and 1-back tasks activated the right cerebellum while the 2-back task activated subcortical regions. Our findings suggest that fitness modulates the effect of aerobic exercise on cognitive function, and provide the first neural evidence to support the influence of fitness on exercise-induced cognitive performance.